A Case Of Intermediate Toxic Epidermal Necrolysis (Lyell Syndrome) Induced By Hydroxychloroquine Sulfate: A Report - Laouali, Salissou; Christiane, Koudoukpo; Harouna, Zaki; Souleymane, Brah M; Hassan, Nouhou (European Scientific Journal, ESJ, 2016)
Malaria is a parasite disease that is endemic in tropical country as Niger (West Africa). Hydroxychloroquine sulfate (HCQ) is a synthetic antimalarial drug that is very often used to treat connective tissue diseases such as, scleroderma, systemic or discoid lupus erythematosus, rheumatoid arthritis. This drug may induce numerous cutaneous adverse reactions as well as the other anti-malarial drugs. We report on a case of intermediate Lyell syndrome that occurred in the first week of treatment of malaria attack with a young woman, aged 19, following the administration of hydroxychloroquine sulfate.